Microtremor observations in Kallang area - Chong, Lit Yung. (2009)
The objective of this project is to investigate the properties of sedimentary layers in the basin by using Microtremor Survey Methods (MSM). To delineate the subsurface structure, the Spatial Auto Correlation method (SPAC method) and the Frequency-Wavenumber method (f-k method) will be used to analyze the microtremors data collected from the field observations in order to obtain the phase velocity dispersion curve, which is a function of subsurface structures. Then, inversion of the dispersion curve produces the estimated subsurface structures. The results will be compared to the summarized results of crosshole PS logging to show the accuracy of these methods. Field observations were carried out in Katong Park (KAT) and Beatty Secondary School (BES). The author will be focus on analyzing the data obtained from BES while his project mate will be focusing on the data collected from KAT. Four data collecting processes were done in BES, involving two small arrays, one medium array and one large array. The inversion of the observed dispersion curves shows that there is a good agreement with the known shear wave velocity profiles of the subsurface. The author is able to delineate the subsurface structure up to at least 40m within an error of 10%. Thus, the author believes that if location and time of the data recording were chosen more wisely, there was a huge possibility the results could be greatly improve. Compare to conventional methods, MSM are comparatively inexpensive, non-invasive, easy-to-perform and time saving. In other words, MSM are very useful tools for microzonation studies because of their simple data acquisition and analysis.